Clustering of non-conducting Kv2.1 channels induces endoplasmic reticulum/plasma membrane junctions and forms cell-surface trafficking hubs - Fox, Philip Douglas, author; Tamkun, Michael M., advisor; Amberg, Gregory C., committee member; Vigh, Jozsef, committee member; Tsunoda, Susan, committee member; Garrity, Deborah M., committee member (Colorado State University. Libraries, 2014)
The voltage-gated K+ channel, Kv2.1, is expressed widely in the mammalian CNS, where it carries the majority of the delayed-rectifier current. The Kv2.1 current facilitates high-frequency action potential firing by promoting the repolarization of the membrane potential and subsequent recovery of voltage-gated Na+ channels from inactivation. Furthermore, Kv2.1 displays a unique cell-surface localization to dense, micron-sized clusters which are sensitive to neuronal insults such as glutamate excitotoxicity. The following dissertation presents original research extending our knowledge of the Kv2.1 K+ channel. The majority of Kv2.1 channels are held in a non-conducting state which is incapable of fluxing K+ in response to membrane potential depolarization. These non-conducting channels tend to localize to the micron-sized clusters which distinguish Kv2.1. Non-conducting, clustered Kv2.1 channels remodel the cortical endoplasmic reticulum (cER) into tight connections with the plasma membrane (PM), likely through a direct interaction. Trafficking of membrane proteins, both exo- and endocytosis are localized to the perimeter of the Kv2.1-induced ER/PM contacts by virtue of remodeling the cER underneath the Kv2.1 clusters. Thus the clustering of Kv2.1 functions to bring protein trafficking and intermembrane signaling together at the neuronal soma.
Keywords: ER/PM junctions; trafficking; potassium channel; non-conducting; Kv2.1; endoplasmic reticulum